Nature of ventricular activation in patients with dilated cardiomyopathy: evidence for bilateral bundle branch block. Issue 2 (August 1994) - Xiao, H B; Roy, C; Gibson, D G
Abstract : OBJECTIVE--To investigate the nature of ventricular activation and its relation with mechanical events in patients with dilated cardiomyopathy. STUDY DESIGN--Retrospective and prospective study with 12 lead electrocardiograms, signal averaged electrocardiograms, and M mode and Doppler echocardiograms. SETTING--Tertiary cardiac referral centre. PATIENTS--77 patients (mean (SD) age 59(13)) with dilated cardiomyopathy, four after aortic valve replacement and three after coronary bypass surgery, and six patients with a normal sized left ventricle and complete right bundle branch block were studied. 15 normal subjects (age 45(20)) were used as controls. RESULTS--In patients with dilated cardiomyopathy, QRS duration was longer (127(25) ms v 90(10), P < 0.05) than normal and was normally distributed (r = 0.991, P < 0.01) on a normal probability plot. 20 had classic left bundle branch block, 29 intraventricular conduction delay, four right bundle branch block, and one bifascicular block. The PR interval was prolonged (185(30) ms v 150(15), P < 0.05). Electromechanical delay, Q to the onset of thickening of the interventricular septum as seen on the transverse M mode echocardiogram, was 75(15) ms in controls, but reduced to 43(15) ms in the patients (P < 0.01). Q to the onset of mitral regurgitation was also short (50(15)) ms, and correlated inversely with PR interval (r = -0.67, n = 73, P < 0.01). Early potentials (< 40 microV) were recorded on the signal averaged electrocardiogram in 33 representative patients and in all controls. Their overall duration was 30(12) ms in the patients, much longer than normal (12(7), P < 0.01)). Early potential time correlated positively with PR interval (r = 0.75, P < 0.01) and QRS duration (r = 0.60, P < 0.01) on a 12 lead electrocardiogram, and negatively with apparent electromechanical delay (r = -0.71, P < 0.01, n = 33), but not with true electromechanical delay (73(15)ms) or true PR interval (163(30)ms), calculated by correcting apparent values for early potential. The onset of left ventricular free wall motion was delayed with respect to the septum beyond 95% of the upper normal limit in all the patients with classic left bundle branch block and intraventricular conduction defect. Motion in the right ventricular free wall was delayed in 13 of 20 patients with left bundle branch block and 24 of 29 with intraventricular conduction defect by 65(20) ms, similar to that (75(10) ms) in patients with right bundle branch block. CONCLUSION--In most patients with dilated cardiomyopathy and an electrocardiographic pattern of left bundle branch block or intraventricular block, the onset of mechanical systole is strikingly and symmetrically delayed in both ventricles, compatible with bilateral bundle branch block. Complete atrioventricular block does not occur. The ventricle is activated through the upper septum and this activation is detectable only by signal averaged electrocardiography. The anatomical substrates for this abnormal activation could be the high connections described by Mahaim and Winston.